Gandhi remains relevant in reshaping the global future - Rajput, J.S. (The Journal of Governance)
The human drive to accelerate the pace of growth and development in the third decade of the 21st century must also embrace a holistic vision of true progress. This calls for a balanced approach that prioritizes sustainability, equity, and innovation. Intriguingly, the very ingenuity that brought artificial intelligence into existence now finds itself in a unique competition with its own creation. As AI continues to redefine industries and challenge conventional norms, it also raises profound questions about human adaptability and creativity. The journey forward lies in harmonizing the strengths of human intelligence with the capabilities of AI. Only then can humanity transform this competition into a collaborative force for advancing civilization.- Reproduced
Keywords: Human, Drive, Growth, Development, Decade, Century, Progress, Sustainability, Equity, Innovation, Ingenuity, Artificial, Intelligence, Competition, Industries, Adaptability, Creativity, Civilization